Mechanical fracture properties of concrete with lunar aggregate simulant - Seitl, Stanislav; Miarka, Petr; Čairović, Iva; Pokorná, Katka; Keršner, Zbyněk; Katzer, Jacek; Zarzycki, Paweł (EDP Sciences, 2020)
From the volumetric point of view, aggregate is the most important ingredient in any kind of concrete. It is impossible to use raw soil instead of aggregate to produce concrete. There are numerous reasons for not using soil for concrete production on Earth, and we should not use lunar soil for concrete production on the Moon for the same reasons. Nevertheless, almost all developed lunar concrete-like composites, such as sulphur or polymeric concretes, are based on raw lunar soil. In the research programme, cement composite based on lunar aggregate simulant was tested. The mechanical fracture properties of the composite were the key point of interest. It was proven that the tested lunar concrete is characterized by stable and uniform properties. The obtained results were compared with the properties of other ordinary cement composites.

From the volumetric point of view, aggregate is the most important ingredient in any kind of concrete. It is impossible to use raw soil instead of aggregate to produce concrete. There are numerous reasons for not using soil for concrete production on Earth, and we should not use lunar soil for concrete production on the Moon for the same reasons. Nevertheless, almost all developed lunar concrete-like composites, such as sulphur or polymeric concretes, are based on raw lunar soil. In the research programme, cement composite based on lunar aggregate simulant was tested. The mechanical fracture properties of the composite were the key point of interest. It was proven that the tested lunar concrete is characterized by stable and uniform properties. The obtained results were compared with the properties of other ordinary cement composites.
Mechanical fracture properties of concrete with lunar aggregate simulant
Keywords: Fatigue; lunar soil aggregate; Fatigue; lunar soil aggregate